Studi Pengelolaan Model Manajemen Pemeliharaan Garpu Tala di PT PLN (Persero) Unit Pelaksana Pelayanan Pelanggan (UP3) Bali Timur - Cahyani, Dewa ayu Nancy; Hartati, Rukmi Sari; Ariastina, Wayan Gde (Majalah Ilmiah Teknologi Elektro, 2019)
PT. PLN in order to ensure the well-maintained reliability of feeders has routinely carried out maintenance of medium voltage networks, which also aims to keep SAIDI SAIFI's indicators well maintained. The different maintenance patterns in each Unit Pelaksana Pelayanan Pelanggan (UP3), inspection schedules that take long periods and rapidly changing environmental. Under these conditions, a method is needed which aims to optimize maintenance.The method will enhance the asset management-based methods with improvements in the inspection by adding ground patrol inspections, enhancement on the duration of optimization and blackout schedules with the integration of work schedules, reporting and daily follow-up of inspection results. The method is named Gerakan ARmada PedUli penyulang dan TindAk Lanjut (GARPU TALA). Based on this thesis the results of the analysis of kWh were saved by simulation if it would be implemented for maintenance from 2017, then it was obtained the saving kWh by 15,182 kWh or Rp. 20.116.150, -.While saving kWh for decrease disruption after the Garpu Tala maintenance method was equal to 71.941 kWh or Rp. 113,377,927.00. The decrease in disturbances was at an average of 30%. While globally, maintenance was more structured and effective and the results were monitored.